Orb-web inclination in Uloboridae spiders: the role of microhabitat structure and prey capture. Issue 5 (3rd September 2017) - Diniz, Suzana; Vasconcellos-Neto, João; Stefani, Vanessa
Abstract : Spider webs are a good example of how phenotypic traits can be adjustable to the physical structure of the environment. Orb-web spiders of the family Uloboridae sometimes form aggregations inside webs of other spider species. In the present study, we focused on the system of Uloboridae associated with webs of the spider Aglaoctenus (Lycosidae). Because of the conformation of Aglaoctenus webs, the direction of prey flow in the central and peripheral positions of the Uloboridae aggregations is vertical and horizontal, respectively. The inclination of Uloboridae orb-webs, in relation to the ground, tends to be closer to horizontal in the centre and vertical in the periphery, whereas other characteristics of the orb-webs and spiders do not differ between the positions. Structural differences between centre and periphery were not enough to explain the inclination pattern of the orb-webs, at least regarding the method we used to measure the micro-habitat structure in this study. Our results support the view of intraspecific variability in orb-web inclination as a case of foraging optimisation strategy and, possibly, of adaptive plasticity.